Adapting cities to the surge: A comprehensive review of climate-induced urban flooding - Dharmarathne, Gangani; Waduge, A.O.; Bogahawaththa, Madhusha; Rathnayake, Upaka; Meddage, D.P.P. (Results in engineering, 2024)
Climate change is a serious global issue causing more extreme weather patterns, resulting in more frequent and severe events like urban flooding. This review explores the connection between climate change and urban flooding, offering statistical, scientific, and advanced perspectives. Analyses of precipitation patterns show clear changes, establishing a strong link between climate change and the heightened intensity of global rainfall events. Hydrological modeling and case studies provide compelling scientific evidence attributing urban flooding to climate-induced changes. Urban infrastructure, including transportation networks and critical facilities, is increasingly vulnerable, worsening the impact on people's lives and businesses. Examining adaptation strategies, the review highlights the need for resilient urban planning and the integration of green infrastructure. Additionally, it delves into the role of advanced technologies, such as artificial intelligence, remote sensing, and predictive modeling, in improving flood prediction, monitoring, and management. The socio-economic implications of urban flooding are discussed, emphasizing unequal vulnerability and the importance of inclusive policies. In conclusion, the review stresses the urgency of addressing climate-induced urban flooding through a holistic analysis of statistical trends, scientific evidence, infrastructure vulnerabilities, and adaptive measures. The integration of advanced technologies and a comprehensive understanding of socio-economic implications are essential for developing effective, inclusive strategies. This review serves as a valuable resource, offering insights for policymakers, researchers, and practitioners striving for climate-resilient urban futures amid escalating climate change impacts. •Reviewed the links between precipitation trends and climate change dynamics.•Examined urban infrastructure susceptibility to changing climate conditions.•Explored innovative adaptive strategies worldwide for urban flood risk reduction.•Suggested future challenges and opportunities in addressing climate-induced urban flooding.